Researching with Children’s Voice Challenges in the Field - Srivastava, Deepti; Shobha, (JOURNAL OF INDIAN EDUCATION, 2014)
The study looked into the contested notion of childhood and its implications for research conducted with children. It located the view of childhood as socially constructed (James and Prout 1997), and delved into the world of street children who stayed in a non-government, non-custodial, voluntary and comprehensive care children’s home in north Delhi. The objectives of the study were to grapple with the theoretical and methodological tensions of engaging in a non-invasive dialogue with the culturally different children in order to locate agency in children’s voice. These voices were heard in the ‘free spaces’ within the institution to minimise the structural constraints imposed by formal spaces. The findings of the study revealed the methodological research challenges including children’s ability to withdraw from situations due to the researcher’s proclivity to under or overestimate the choice of tools. It also showed how children constantly engaged, reflected, manipulated and guarded themselves in their social worlds and brought forth the need to understand these negotiations within similar spaces in the formal school context, in addition to observations within the classrooms, to understand the agency in children’s voice.